Zasady techniki prawodawczej w Polsce i Unii Europejskiej - Stępniak, Kamil (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This paper is acomplex summary of problematic principles of legislation technique. European law-making has abig meaning in Polish law. These dual systems affect each other. The principles of legislative techniques in Poland are regulated by the Regulation of the Prime Minister, but not always. Sometimes they were set in abook form.The rules of legislative technique are of great importance for understanding of legislation and the entire legal system. Thanks to them the legislators know what editorial units used in individual acts. Understanding them often allows for better application of the law. European Union Law has its own standards and its own legislative rules. Correlation of Polish law with the European reveals itself even when it is necessary to transpose the EU directives. The method and quality of establishing law in the European Union somehow directly affect the rights in Poland. Therefore, distinguish between the two legal systems and learn how to use them.This paper describes the importance of the principles of correct legislation for both the national agenda, as well as for the European law. It identifies the main concepts. It allows the reader to explore correlations principles of legislative techniques in the EU and Poland.
Keywords: techniki prawodawcze; Polska; Unia Europejska